Trade Liberalization in Fund-Supported Programs - Sharer, Robert; Sorsa, Piritta (Washington, D.C. : International Monetary Fund, 1998)
This study asseses trade liberalization in programs supported by the IMF by reviewing multiyear arrangements in the 1990s and six detailed case studies. It also discusses the main economic factors affecting trade policy targets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet